Effect Of Sports Practice In Reducing Hyperactivity In Deaf Children (12-18 Years) - Torki , Ishak; Djouadi , Khalde; Valkova, Hana (sports creativity, 2025)
The present study aimed to try to identify the extent of the effect of sports practice in reducing hyperactivity in dumb deaf children. In this study, the researchers relied on a descriptive approach. The study sample also included 25 deaf children who were deaf from the age group (11-17 years) of both sexes. They belong to the pedagogical centers in the state of M'sila. They were divided into two groups, the first group is practicing sports made up of 12 children, while the second group is not practicing sports made up of 13 children. As a tool for the study, the researchers relied on building a questionnaire based on previous studies. Among the most important findings is that exercise has a positive effect in reducing hyperactivity and hyperactivity in dumb deaf children